AntarcticaLC2000: The new Antarctic land cover database for the year 2000 - Hui, FengMing; Kang, Jing; Liu, Yan; Cheng, Xiao; Gong, Peng; Wang, Fang; Li, Zhan; Ye, YuFang; Guo, ZiQi (Zenodo, 2017)
Antarctic Land Cover Database for the Year 2000 (AntarcticaLC2000) was produced using Landsat Enhanced Thematic Mapper Plus (ETM+) data acquired around 2000 and Moderate Resolution Imaging Spectrometer (MODIS) images acquired in the austral summer of 2003/2004 according to the criteria for the 1:100,000-scale. Three land cover types were included in this map, separately, ice-free rocks, blue ice, and snow/firn. This classification legend was determined based on a review of the land cover systems in Antarctica (LCCSA) and an analysis of different land surface types and the potential of satellite data. Image classification was conducted through a combined usage of computer-aided and manual interpretation methods. Results show that the areas and percentages of ice-free rocks, blue ice, and snow/firn are 73,268.81 km 2 (0.537%), 225,937.26 km 2 (1.656%), and 13,345,460.41 km 2 (97.807%), respectively. The comparisons with other different data proved a higher accuracy of our product and a more advantageous data quality. Please help maintaining this service by properly citing and acknowledging if you use the data for publications: Hui, F., J. Kang, Y. Liu, X. Cheng, P. Gong, F. Wang, Z. Li, Y. Ye, and Z. Guo. 2017. "AntarcticaLC2000: The new Antarctic land cover database for the year 2000." SCIENCE CHINA Earth Sciences 60: 686-696. doi:10.1007/s11430-016-0029-2.